Load‐independent harmonic mitigation in SCR‐fed three‐phase multiple adjustable speed drive systems with deliberately dispatched firing angles. Issue 4 (16th February 2018) - Yang, Yongheng; Davari, Pooya; Blaabjerg, Frede; Zare, Firuz
Abstract : Adjustable speed drives (ASD) are widely used in industry for energy savings, where low‐cost diode rectifiers are still employed as the front‐ends, also for simplicity in control and reliability in operation. However, significant harmonics appear at the grid, which should be tackled according to standards and/or grid‐connection rules. If not, a poor power quality will cause the efficiency of the entire system drop. Currently, communication technologies are still not very cost‐effective for industrial harmonic control in multiple parallel motor‐drive systems. Therefore, this study proposes a harmonic mitigation strategy for multiple ASD systems, where silicon‐controlled rectifiers (SCR) with boost converters in the dc‐link have been adopted to increase the harmonic‐current controllability. More specific, the SCR firing angles are deliberately dispatched among the drive units, which results in certain phase shifts of the SCR currents on purpose. Consequently, the harmonics appearing in the grid current can be mitigated to some extent without communication. The effectiveness is independent of an individual SCR system loading when a number of drives are connected. Simulations are carried out to verify the discussion. Furthermore, to maximize the harmonic cancellation, a customised modulation scheme has been experimentally demonstrated. Both simulation and experimental results have confirmed the analysis.